G322(P) The sepsis trust screening action tool: concerns about utility and application. (May 2019) - Wallace, S; Chapman, A; Khan, A; Bangalore, S; Williams, B
Abstract : Aims: To ascertain whether the parameters on the Sepsis Trust screening and action tool, a tool to help clinical staff recognise and treat sepsis swiftly, are useful indicators of septic children. Methods: We undertook retrospective application of the screening tool combined with case note reviews of randomly selected children attending paediatric ED and of children with proven bacteraemia. Results: One hundred patients were identified randomly from children attending ED in April 2018. Ninety-five patients' notes were traceable and were reviewed. The ages ranged from two days to 15 years old; median age was two year. Thirty-one of the 95 would have triggered at least one red flag for sepsis. 31 children triggered on severe tachycardia, 13 on severe tachypnoea. Two appeared sick to the health professional and were put on non-invasive ventilation and antibiotics. Seven children had blood cultures taken- all were negative. Positive paediatric blood culture data for children presenting to ED in our hospital in 2017 were reviewed by a microbiologist and a paediatrician; those felt to be contaminants were excluded. There were thirty- seven children with proven bacteraemia (age range 2 days – 15 years old; median age of 12 months). Six children did not trigger any red flags (4 grew S. Typhi, 1 s . Aureus, 1 Acinetobacter Baumanii ), eight triggered one red flag and the remainder scored two or more red flags. The range of red flags triggered was 0–8 (median 2). The red flag most frequently triggered in those with bacteraemia was appearing unwell to treating clinician. Conclusion: Application of the red flag trigger on Sepsis Trust Tool would have led 31/95 children attending our ED to receive immediate intravenous antibiotics, the majority unnecessarily. The most frequently triggered red flag was tachycardia which can be influenced by fever, anxiety and crying, especially in young age group. The children with proven bacteraemia and sepsis did not consistently trigger red flags. These findings combined suggest that that the Sepsis Trust Screening Action Tool has little clinical utility in our population and should not be used in its current form; clinical acumen remains key to recognition of sepsis.